2021
DOI: 10.3389/fchem.2021.779976
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin Conjugates With Multiple Clickable Amino Acids Encoded by C-Terminal Engineered Pyrrolysyl-tRNA Synthetase

Abstract: This study reports the application of expanding genetic codes in developing protein cage-based delivery systems. The evolved Methanosarcina mazei pyrrolysyl-tRNA synthetase (PylRS)•tRNAPyl pairs derived from directed evolution are examined to probe their recognition for para-substituted phenylalanine analogs. The evolved MmPylRS, AzFRS, harboring a wide range of substrates, is further engineered at the C-terminal region into another variant, AzFRS-MS. AzFRS-MS shows suppression of the elevated sfGFP protein am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…Sun et al, 2021; X. Zhang et al, 2019) that can be tested in PCPs. More advanced modifications would allow selective binding to cells other than those presenting TfR1 (Wang et al, 2021). Additionally, drug‐loaded ferritin particles can be coupled to probes such as cell membrane‐binding peptides (Wang et al, 2021) via N‐terminal SNAP‐tag fusions, allowing their rapid deployment as targeted theranostics (Padayachee et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun et al, 2021; X. Zhang et al, 2019) that can be tested in PCPs. More advanced modifications would allow selective binding to cells other than those presenting TfR1 (Wang et al, 2021). Additionally, drug‐loaded ferritin particles can be coupled to probes such as cell membrane‐binding peptides (Wang et al, 2021) via N‐terminal SNAP‐tag fusions, allowing their rapid deployment as targeted theranostics (Padayachee et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…More advanced modifications would allow selective binding to cells other than those presenting TfR1 (Wang et al, 2021). Additionally, drug‐loaded ferritin particles can be coupled to probes such as cell membrane‐binding peptides (Wang et al, 2021) via N‐terminal SNAP‐tag fusions, allowing their rapid deployment as targeted theranostics (Padayachee et al, 2019). Drug‐loaded ferritin nanocarriers are highly versatile, and the low‐cost production method presented here could be expanded to supply researchers working on tumor‐targeted drug delivery nanoformulations with the necessary quantities of protein.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the inner surface of the ferritin nanocage may be engineered by genetically fusing hydrophobic peptides to the C-terminal end of ferritin subunits to increase absorption of insoluble, hydrophobic cargo [ 111 , 112 ]. Introducing cysteine residues to the interior of the nanocage has been a widely used approach to facilitate covalent attachment of dye molecules, drugs, or other active compounds through disulfide bonds [ 113 ] or to enable specific chemical reactions such as copper-free click chemistry [ 114 ].…”
Section: Interior Modificationsmentioning
confidence: 99%
“…The interior nanoparticle surface is commonly modified to encapsulate specific materials (Figure E). It has been widely demonstrated that mutating interior-facing surface residues to hold a net charge facilitates electrostatic-mediated cargo encapsulation (e.g., encapsulation of supercharged fluorescent proteins or nucleic acids) (Figure E). ,, Interior surface residues can also be mutated to include side chains capable of specific chemical reactions like copper-free click chemistry . Alternatively, larger domains like affinity peptides can be seamlessly integrated into the protein nanoparticle interior through genetic fusion.…”
Section: Part 1: Designable Features Of Protein Nanoparticlesmentioning
confidence: 99%
“…18,55,83 Interior surface residues can also be mutated to include side chains capable of specific chemical reactions like copper-free click chemistry. 84 Alternatively, larger domains like affinity peptides can be seamlessly integrated into the protein nanoparticle interior through genetic fusion. Genetic fusion of functional domains to the nanoparticle interior surface can either be bioactive themselves or enable specific cargo encapsulation such as mRNA and siRNA sequences.…”
Section: ■ Introductionmentioning
confidence: 99%